The clash between the employee’s right to privacy and freedom of expression and social media misconduct: What justifies employee’s dismissal to be a fair dismissal? - Phungula, Simphiwe P (Obiter, 2020)
The 21st century has an increase in the use of the internet as a means of trading. The use of the internet has also influenced the use of social media as a means of communication. This communication extends to the employer–employee relationship in the workplace. However – in South Africa – due to the rapid use of social media both in and out of the workplace, it has become blurry of what constitutes social media misconduct for which an employee may be disciplined. This is exacerbated by the lack of specific legislation dealing with employees and social media misconduct in South Africa. This article deals with the blessings and the curse of using social media as a means of communication in the workplace. It reveals the difficulties faced by both employers and employees when determining to what extent the behaviour of an employee can constitute adequate grounds for dismissal in relation to that employee’s social media misconduct. Recommendations are made on the way forward.